Optimal impulse control of a SIR epidemic - Piunovskiy, Alexey (2020)
Based on our recent results on the optimal impulse control, we solve explicitly an optimal isolation problem for a specific SIR (susceptible-infective-removed) epidemic model describing, eg, the spread of AIDS.